Implementation of the Clinical Pathway Paradigm in Achieving Cost-Effectiveness in Health Financing (Systematic Literature Review): Clinical Pathway Paradigm in Achieving Cost-Effectiveness in Health Financing - Yohanes Firmansyah; Handar Subhandi Bakhtiar (Jurnal Medika Hutama, 2022)
Background: Clinical Pathway (CPW) is a clinical documentation technique that focuses on clinical practice standards for nurses, physicians, and others. The clinical pathway is a two-way instruction for handling patients on clinical problems, diagnosis, and stages of care. Any intervention given and the development of the patient is documented systematically based on the time criteria set and expected to increase the service quality and lower hospital expenses. This paper aimed to measure the CP role in increasing hospital expenses efficiency. Methods: A systematic literature review was conducted to determine the effectiveness and efficiency of using clinical pathways for financing. The inclusion criteria were all types of research from descriptive to Randomized Controlled Trials containing at least 2 methods of comparison of interventions published in the last 30 years. Results: This review found 129 articles related to the relationship between clinical pathway use and the effectiveness of financing in hospitals. After going through the screening process based on the inclusion and exclusion criteria, it was found that only 15 articles met the requirements. After analyzing the data, the use of Clinical Pathway in managing patients can lower hospital expenses. Conclusion: Implementing a clinical pathway for patients’ management in hospitals can increase hospital expenses efficiency.